Behavioral Outcomes Differ between Rotational Acceleration and Blast Mechanisms of Mild Traumatic Brain Injury - Stemper, Brian D.; Shah, Alok S.; Budde, Matthew D.; Olsen, Christopher M.; Glavaski-Joksimovic, Aleksandra; Kurpad, Shekar N.; McCrea, Michael; Pintar, Frank A. (Frontiers in Neurology, 2016)
Mild traumatic brain injury (mTBI) can result from a number of mechanisms, including blunt impact, head rotational acceleration, exposure to blast, and penetration of projectiles. Mechanism is likely to influence the type, severity, and chronicity of outcomes. The objective of this study was to determine differences in the severity and time-course of behavioral outcomes following blast and rotational mTBI. The Medical College of Wisconsin (MCW) Rotational Injury model and a shock tube model of primary blast injury were used to induce mTBI in rats and behavioral assessments were conducted within the first week, as well as 30 and 60 days following injury. Acute recovery time demonstrated similar increases over protocol-matched shams, indicating acute injury severity equivalence between the two mechanisms. Post-injury behavior in the elevated plus maze demonstrated differing trends, with rotationally injured rats acutely demonstrating greater activity, whereas blast-injured rats had decreased activity that developed at chronic time points. Similarly, blast-injured rats demonstrated trends associated with cognitive deficits that were not apparent following rotational injuries. These findings demonstrate that rotational and blast injury result in behavioral changes with different qualitative and temporal manifestations. Whereas rotational injury was characterized by a rapidly emerging phenotype consistent with behavioral disinhibition, blast injury was associated with emotional and cognitive differences that were not evident acutely, but developed later, with an anxiety-like phenotype still present in injured animals at our most chronic measurements.